LWW's foundations in sterile products for pharmacy technicians - Acosta, W. Renee (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
LWW's foundations in sterile products for pharmacy technicians is the essential resource on sterile products for pharmacy technician students and their instructors.
Sterile product basics -- Preventing contamination -- Sterile product calculations -- Delivery systems equipment -- Environment -- Basic aseptic techniques -- Making sterile preparations -- Basic sterile preparations -- Quality assurance
Includes bibliographical references and index.
Keywords: DRUGS -- STERILIZATION